2021
DOI: 10.1111/nep.13855
|View full text |Cite|
|
Sign up to set email alerts
|

Differential expression analysis of urinary exosomal circular RNAs in patients with IgA nephropathy

Abstract: Aims Immunoglobulin A nephropathy (IgAN) is the most common primary glomerular disease to cause end‐stage kidney disease. This study investigated the difference in urinary exosomal circular RNA (circRNA) expression profiles between patients with IgAN and healthy controls (HCs), for better understanding of gene regulation in exosomes of IgAN patients. Methods A pairwise comparison of urinary circRNA expression profiles between IgAN patients and HCs was performed using methods, including high‐throughput sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The study regarding sEV-circRNAs involvement in the diagnosis of IgAN is only just emerging from its infancy. Luan et al (2021) have showed a total of seven urinary sEV-circRNAs (circRNAchr18: 45391430-45423180-, circRNAchr22:22153301-22162135-, circRNAchr1:243708812-243736350-, circRNAchr19:42740758-42744294-, circRNAchr17:11984673-12016677+, circRNAchr18: 11862394-11876687+ and circRNAchr17:8409636-8413,267-) were significantly upregulated in IgAN patients. Gene ontology (GO) analysis demonstrated that the above-mentioned sEV-circRNAs may be involved in primary miRNA processing, the ability of angiotensin receptor binding, and stress fiber function.…”
Section: Roles Of Sev-circrnas In Iganmentioning
confidence: 99%
“…The study regarding sEV-circRNAs involvement in the diagnosis of IgAN is only just emerging from its infancy. Luan et al (2021) have showed a total of seven urinary sEV-circRNAs (circRNAchr18: 45391430-45423180-, circRNAchr22:22153301-22162135-, circRNAchr1:243708812-243736350-, circRNAchr19:42740758-42744294-, circRNAchr17:11984673-12016677+, circRNAchr18: 11862394-11876687+ and circRNAchr17:8409636-8413,267-) were significantly upregulated in IgAN patients. Gene ontology (GO) analysis demonstrated that the above-mentioned sEV-circRNAs may be involved in primary miRNA processing, the ability of angiotensin receptor binding, and stress fiber function.…”
Section: Roles Of Sev-circrnas In Iganmentioning
confidence: 99%
“…IgA nephropathy (IgAN) is the most common type of primary glomerulonephritis worldwide. To date, only two studies have analyzed the dysregulated circRNAs profiles in IgAN patients ( 72 , 73 ). The first study conducted circRNA sequencing using RNA isolated from peripheral blood mononuclear cells (PBMCs) of three pairs of IgAN patients and healthy controls ( 72 ).…”
Section: Circrnas As Novel Biomarkers For Kidney Diseasesmentioning
confidence: 99%
“…A total of 145 circRNAs were identified as differentially expressed, among which 112 circRNAs were up-regulated while 33 were down-regulated in IgAN group compared to controls. A recent study investigated the circRNAs profiles in urinary exosomes from five pairs of IgAN patients and healthy controls by high-throughput RNA sequencing ( 73 ). In total, 1,322 circRNAs were detected in the urinary exosomes and 476 were aberrantly expressed, including 450 up-regulated and 26 down-regulated circRNAs.…”
Section: Circrnas As Novel Biomarkers For Kidney Diseasesmentioning
confidence: 99%
“…Unlike other ncRNAs, knowledge about circRNAs in kidney diseases is still in the nascent stage. Studies have reported dysregulation of circRNAs in AKI ( Xu et al, 2020a ), diabetic nephropathy ( Bai et al, 2020 ), immunoglobulin A nephropathy ( Luan et al, 2021 ), autoimmune kidney disease ( Zhang et al, 2021 ), and renal malignancies ( Cen et al, 2021 ). While circRNAs are believed to participate in the fibrotic process ( Liu et al, 2019 ), their specific functions in renal fibrosis remain largely uncharacterized.…”
Section: Introductionmentioning
confidence: 99%